2009
DOI: 10.1002/jmri.21887
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience on utility of gadobenate dimeglumine (Gd‐BOPTA) enhanced T1‐weighted MR cholangiography in diagnosis of acute cholecystitis

Abstract: PurposeTo investigate the feasibility of the use of gadobenate dimeglumine (also known as Gd‐BOPTA) ‐enhanced T1‐weighted MR cholangiography in diagnosis of acute cholecystitis.Materials and MethodsThis prospectively designed institutional review board‐approved HIPAA‐compliant study was done between January and November 2007. We included 11 consecutive patients (7 male, mean age 59 years) who presented to the emergency room with acute right upper quadrant pain and with equivocal physical examination and/or ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Previous authors have demonstrated the potential efficacy of MR cholangiography utilizing Mangafodipir trisodium and Gd-BOPTA in the diagnosis of cholecystitis [18][19][20], however, these studies have extended imaging well beyond the standard 30 min imaging window. Morphologic features of cholecystitis on MR have also been established [21,22], but if MR is to play a significant role in the diagnosis of cholecystitis, it must be able to demonstrate cystic duct patency, and gallbladder reflux via functional evaluation akin to hepatobiliary scintigraphy.…”
mentioning
confidence: 94%
“…Previous authors have demonstrated the potential efficacy of MR cholangiography utilizing Mangafodipir trisodium and Gd-BOPTA in the diagnosis of cholecystitis [18][19][20], however, these studies have extended imaging well beyond the standard 30 min imaging window. Morphologic features of cholecystitis on MR have also been established [21,22], but if MR is to play a significant role in the diagnosis of cholecystitis, it must be able to demonstrate cystic duct patency, and gallbladder reflux via functional evaluation akin to hepatobiliary scintigraphy.…”
mentioning
confidence: 94%
“…Recently, a potential role for T1-weighted MR cholangiography using agents that are both extracellular and hepatocyte specific with increased biliary excretion in the diagnosis of acute cholecystitis has been described. 121,122 This technique allows for functional evaluation as in hepatobiliary scintigraphy; however, further investigation in this application is needed.…”
Section: Imagingmentioning
confidence: 98%
“…MRG akut kolesistitin saptanmasında, BT ve US'deki bulgulara benzer bulguları ile sensitif bir yöntemdir. Manyetik rezonans kolanjiyopankreatografi (MRKP) safra kesesi boynundaki veya sistik kanaldaki taşı gösterebilir [28].…”
Section: Akut Kolesistitunclassified